Communication challenges experienced by veterinary professionals during the COVID‐19 pandemic. Issue 1 (12th October 2021) - Quain, A; Mullan, S; Ward, MP
Abstract : The COVID‐19 pandemic and associated restrictions have caused major changes in veterinary practice. Utilising a subset of qualitative data from a global survey of 540 veterinarians, veterinary nurses and animal health technicians, we highlight the impact of these changes on communication in veterinary clinical practice. Communication challenges experienced by veterinary team members included lack of face‐to‐face contact with clients; increased difficulty in communicating in general; inability to demonstrate physical examination, diagnostic findings or treatment information to clients; difficulty in communicating while wearing personal protective equipment; increased 'miscommunication' and challenges in convincing clients of the importance of pandemic‐associated protocols. These findings suggest a need for veterinary teams to modify and adapt their communication strategies to facilitate effective communication where social distancing and noncontact consultations are required.